Assessment of decadal changes in coastal nitrogen sources in NW Spain with stable isotopes in macroalgae and mussels - Antonio Bode; Rita García-Seoane; Zulema Varela; Inés G. Viana (PLoS ONE, 2025)
Upwelling is one of the major mechanisms responsible for the input of nutrients sustaining high levels of marine primary production. As a consequence of global change, variations in upwelling intensity may affect nutrient supply thus impacting marine food webs. In this study, we examine the effects of decadal variability of upwelling strength on nitrate supply and its influence on the nitrogen stable isotope composition at the base of the marine food web at the northern boundary of the Canary Current upwelling system (NW Spain) between 1989 and 2023. The study focused on the early upwelling season each year (March-June) to minimize the effects of nitrogen remineralization. Intertidal macroalgae (Phaeophyceae) and mussels (Mytilus galloprovincialis) were used as proxies for temporally integrated isotopic signals of nitrogen sources (δ15N). While no significant temporal trends for either upwelling strength, nitrate concentrations, or stable isotopes were found, three periods with characteristic upwelling and nutrient regimes were identified. A linear increase in δ15N, particularly in Fucus spp., associated with a decreasing contribution of upwelling-derived nitrogen suggest the influence of additional sources, likely of anthropogenic origin. Thus, no net change in productivity would be expected in this region despite quasi-decadal shifts in upwelling dynamics. Further insights on the origin and relevance of these sources can be gained through the investigation of river and runoff inputs and the use of more sensitive tracers, such as amino acid δ15N analysis in mussels.